Testing system analysis as form of monitoring on course “Computer informational technologies” (on base of Distant Learning System “Kherson Virtual University ”) (Journal of Information Technologies in Education (ITE), 2007)
In the article the usage of computer testing technologies for current and final examinations in the course “Computer information technologies ” for students of 1st course is considered.